KONTRIBUSI MINAT BELAJAR DAN PEMANFAATAN SARANA PRASARANA LABORATORIUM TERHADAP HASIL BELAJAR SISWA - Az Rohmi; Delsina Faiza (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This study aims to reveal how much the contribution of learning interest and the utilization of laboratory facilities together and individually on learning outcomes. The type of this research is descriptive correlational research using simple random sampling technique for sampling, so that the sample used is as many as 40 people from the population, amounting to 67 students of class X TAV in SMK Negeri 2 Solok. The research method used is in two ways, namely with documentation and questionnaires / questionnaires. Data analysis test results showed (1) Interest in learning contributed significantly to the learning outcomes of Class X TAV students of SMK Negeri 2 Solok by 11.83%, (2) Utilization of laboratory infrastructure contributed significantly to the learning outcomes of Class X TAV students of SMK Negeri 2 Solok amounted to 15.84%, (3) The interest in learning and the utilization of laboratory infrastructure together contributed significantly to the learning outcomes of class X TAV of SMK Negeri 2 Solok at 34.92%. So it can be concluded that the interest in learning and utilizing laboratory infrastructure contributes significantly to the learning outcomes of class X TAV students at SMK Negeri 2 Solok, the higher the interest in learning and the maximum utilization of laboratory infrastructure means the higher the learning outcomes.Keywords: Interest in Learning, Use of Laboratory Infrastructure, Learning Outcomes